2000
DOI: 10.1103/physreve.63.016402
|View full text |Cite
|
Sign up to set email alerts
|

Metallization of hydrogen using heavy-ion-beam implosion of multilayered cylindrical targets

Abstract: Employing a two-dimensional simulation model, this paper presents a suitable design for an experiment to study metallization of hydrogen in a heavy-ion beam imploded multilayered cylindrical target that contains a layer of frozen hydrogen. Such an experiment will be carried out at the upgraded heavy-ion synchrotron facility (SIS-18) at the Gesellschaft für Schwerionenforschung, Darmstadt by the end of the year 2001. In these calculations we consider a uranium beam that will be available at the upgraded SIS-18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 20 publications
0
42
0
Order By: Relevance
“…Significant progress has been made to study certain aspects of the EOS of hydrogen and deuterium under such extreme conditions, but the final goal of achieving metallized hydrogen has not yet been reached. Previously, we demonstrated with the help of numerical simulations that an intense heavy ion beam can be a very efficient additional laboratory tool to study this problem [2]. The beam-target geometry is shown in Fig.5.…”
Section: Compression Of Hydrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant progress has been made to study certain aspects of the EOS of hydrogen and deuterium under such extreme conditions, but the final goal of achieving metallized hydrogen has not yet been reached. Previously, we demonstrated with the help of numerical simulations that an intense heavy ion beam can be a very efficient additional laboratory tool to study this problem [2]. The beam-target geometry is shown in Fig.5.…”
Section: Compression Of Hydrogenmentioning
confidence: 99%
“…Numerical simulations [2] and analytic studies [3] have shown that using such a scheme one may access theoretically predicted physical conditions necessary to achieve hydrogen metallization. These include a density of 1 -2 g/cm 3 , a pressure of 3 -10 Mbar and a temperature of a few thousand K. The beam parameters were considered to be that of the beam that will be generated at the future SIS100 facility at the GSI.…”
Section: Introductionmentioning
confidence: 98%
“…In laser-driven inertial fusion research, a sophisticated smoothing system using distributed phase-plate technology has been developed [3]. Recently, a similar technology using oscillating wobbler fields has been proposed for ion-beam-driven inertial fusion energy [1,[4][5][6][7][8][9][10]] to achieve the desired uniform illumination over an annular region (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In laser-driven inertial fusion research, a sophisticated smoothing system using distributed phase-plate technology has been developed [3]. Recently, a similar technology using oscillating wobbler fields has been proposed for ion-beam-driven inertial fusion energy [1,[4][5][6][7][8][9][10]] to achieve the desired uniform illumination over an annular region (see Fig. 1).…”
Section: Introductionmentioning
confidence: 99%